Topical Application of Temperature-Sensitive Gel Containing Caerin 1.1 and 1.9 Peptides on TC-1 Tumour-Bearing Mice Induced High-Level Immune Response in the Tumour Microenvironment - Ni, Guoying; Liu, Xiaosong; Li, Hejie; Fogarty, Conor E.; Chen, Shu; Zhang, Pingping; Liu, Ying; Wu, Xiaolian; Wei, Ming Q.; Chen, Guoqiang; Zhang, Ping; Wang, Tianfang (Frontiers in Oncology, 2021)
The development of topical cream drugs that increase immune activation of tumour-infiltrating lymphocytes against tumour and chronic viral infection-associated lesions is of great immunotherapeutic significance. This study demonstrates that the topical application of a temperature-sensitive gel containing caerin 1.1 and 1.9 peptides reduces nearly 50% of the tumour weight of HPV16 E6/E7 transformed TC-1 tumour bearing mice via improving the tumour microenvironment. The confocal microscopy confirms the time-dependent penetration of caerin 1.9 through the epidermal layer of the ear skin structure of mice. Single-cell transcriptomic analysis shows that the caerin 1.1/1.9 gel expands the populations with high immune activation level, largely stimulates the pro-inflammatory activity of NK and dendritic cells. Closely associated with INFα response, Cebpb seems to play a key role in altering the function of all Arg1hi macrophages in the caerin group. In addition, the caerin gel treatment recruits almost two-fold more activated CD8+ T cells to the TME, relative to the untreated tumour, which appears a synergistic effect derived from the regulation of S1pr1, Ccr7, Ms4a4b, and Gimap family expression. The TMT10plex-labelling proteomic quantification further demonstrates the activation of interferon-alpha/beta secretion and response to cytokine stimulus by the caerin gel, while the protein contents of several key regulators were elevated by more than 30%, such as Cd5l, Gzma, Ifit1, Irf9 and Stat1. Computational integration of the proteome with the single-cell transcriptome consistently suggested greater activation of NK and T cells with the topical application of caerin peptide gel.